Pengarusutamaan Paradigma Inklusif dalam Ekosistem Pendidikan Islam di Tengah Gejala Intoleransi Pelajar Muslim - Hakim, Luqman; Mursyid, Abdul Bar; Bahja, Ahmad Wildan Thobibi; Masud, Ali (CENDEKIA, 2023)
This article departs from the growing symptoms of intolerance among Indonesian Muslim students, especially at the high school (SMA/MA) and university levels. They seem to have difficulty appreciating differences in religious practices in society, both those shown by minority Muslim groups and other religious communities. Statistically, they tend to be very intolerant towards minority Muslim groups (51.1%), rather than towards followers of other religions (34.3%). This research is qualitative in type by adopting a library research approach. The main focus of this research is to analyze the factors that cause the emergence of symptoms of intolerance among Muslim students and how the inclusive paradigm is able to make the Islamic education ecosystem more open to diversity. The findings in this research indicate that the growing cases of intolerance among Muslim students originate from at least three factors. First: the increasingly intense dissemination of religious exclusivism in public spaces and social media by Islamist groups. Second: the style of Islamic literature in high schools (SMA/MA) and universities still does not emphasize the importance of tolerance in social life. Third: the tendency of educators toward religious learning patterns that are doctrinal-normative rather than contextual-progressive. Of these three factors, at least it emphasizes the need to bring an inclusive paradigm into the Islamic education ecosystem. This effort can be achieved by: 1). reformulate the Islamic education curriculum based on a multicultural paradigm, 2). carry out intensive dissemination of the understanding of national tolerance to educators, 3). designing PAI learning strategies that are responsive to diversity.